STRUCTURAL LAKE DECODING IN NORTH-WESTERN PART OF BELARUS ACCORDING TO SPACE PHOTOS - V. I. Mikhailov (Наука и техника)
The paper contains an experience of structural lake decoding according to space photos. The obtained data make it possible to reveal some genetic peculiar features in location of lakes and explain their direct relation to manifestation of tectonic motions in the Earth’s crust. The paper permits to use the decoding results for various practical purposes.